UPAYA PENERAPAN REUSE, REDUCE, RECYCLE (3R) DAN PENGETAHUAN MASYARAKAT TERHADAP PENGELOLAAN SAMPAH PLASTIK DI DESA BERINGIN TELUK KUANTAN TAHUN 2020 : REUSE,REDUCE,RECYCLE (3R) APPLICATION EFFORTS AND COMMUNITY KNOWLEDGE OF PLASTIC WASTE MANAGEMENT IN BERINGIN VILLAGE TELUK KUANTAN KECAMATAN KUANTAN TENGAH IN 2020 - Fifi Ayulia; Nurhapipa Nurhapipa; Hayana Hayana (Media Kesmas (Public Health Media), 2021)
The effort to implements 3R is an effort made to manage plastic waste produced by the community so that the plastic waste they produce every day. In addition, the people in the village, even though the result of the combustion are dangerous for health. The purpose of this study was the determine the efforts to apply 3R and public knowledge of plastic waste management in Beringin village teluk kuantan in 2020. This research is a descriptive quantitative study with a cross sectional approach. Conducted by distributing questionnaires and field observation to 88 respondents by purposive sampling. Research location in the Beringin village teluk kuantan in may 2020. The results showed that the p-value > ? (0.05) with the p-value application of reduce variable (0.009), the p-value application of reuse (0.007), application of recycle p-value (0.010) and knowledge p-value (0.002). From the results of the study it can be concluded that all variabels have a relationship between the application of reuse, reduce, recycle dan public knowledge of plastic waste management in Beringin village teluk kuantan in 2020. And researchers suggest that government should invite the public to manage plastic waste in particular so that it can be used as an item that produces economic value.